Metallic spacers to enhance membrane distillation - Tan, Yong Zen (2020)
Despite membrane distillation (MD) being well acknowledged as a green technology due to the capability to treat water using waste heat, the efficient use of this heat remains one of the biggest challenge for MD to be cost-effective. In this study, we harnessed the high thermal conductivity of metallic spacers to improve the energy efficiency in DCMD, with the performance studied via both simulations and experiments. The frequently used polypropylene spacer with each mesh dimension of 3 mm was used as a benchmark for comparison. Two metals were investigated, (namely, nickel and copper), along with three spacer densities (namely, 3 mm mesh, 1.5 mm mesh and foam). The noteworthy results include: (i) the metallic spacers placed on the feed side of the membrane gave higher temperatures that were more uniform along the membrane surface; (ii) whereas the surface-averaged membrane temperature for the polypropylene material decreased with spacer density, that for the metallic materials decreased then increased with spacer density; (iii) although the experimental distillate fluxes were similar, the heater input energy per unit volume distillate was lower for the metallic foam spacers by up to 16%; and (iv) platinum-coated Ni foam gave a remarkable reduction in energy input of 28% under light irradiation. This study demonstrated the feasibility of using metallic spacers with inherent high thermal conductivity to improve energy efficiency, providing a new platform for further improvements through other commercially available metallic foams or spacer modifications.